COMPARATIVE INVITRO RELEASE OF DICLOFENAC SODIUM GEL FROM DIFFERENT MARKETED PRODUCTS: Pharmaceutical Science-Pharmaceutics - PRABHA, K.SURIA; CH.RAMAKRISHNA; M.SRIVANI; V.N.PRIYANKA; Y.BINDU PRIYA (International Journal of Life Science and Pharma Research, 2012)
Diclofenac Sodium, a non steroidal anti-inflammatory agent is frequently prescribed for the long term treatment of rheumatoid arthritis, osteoarthritis and ankylosing spondylitis. The drug undergoes substantial first pass effect and only 50% of drug is available systemically. Further, the drug is known to induce ulceration and bleeding of the intestinal wall. To avoid the adverse effect, alternate routes of administration have been tried by investigators. Diclofenac Sodium, a non steroidal anti-inflammatory agent is frequently prescribed for the long term treatment of rheumatoid arthritis, osteoarthritis and ankylosing spondylitis. The drug undergoes substantial first pass effect and only 50% of drug is available systemically. Further, the drug is known to induce ulceration and bleeding of the intestinal wall. To avoid the adverse effect, alternate routes of administration have been tried by investigators. The need of the present work aim to compare the invitro release of diclofenac sodium from different marketed products. Four different marketed formulations (A, B, C, D) were studied for their permeation through the dialysis membrane. The Franz diffusion cell was used to determine the amount of the drug diffused from different formulations. The samples were analyzed spectrophotometrically at a wavelength of 276 nm. In vitro release studies were recorded for a four hour period. It was concluded that product C released high rate i.e. 86% of diclofenac sodium within 50 minutes which was also found to be economic when compared to other marketed products.